Investigation of the effects of unilateral total salpingectomy on ovarian proliferating cell nuclear antigen and follicular reserve: experimental study - Atilgan, Remzi; Kuloglu, Tuncay; Boztosun, Abdullah; Orak, Ugur; Baspinar, Melike; Can, Behzat; Sapmaz, Ekrem (Elsevier Science Bv, 2015)
Objective: We aimed to investigate the effects of unilateral total salpingectomy procedure on ovarian follicular reserve, apoptosis, and proliferating cell nuclear antigen (PCNA) staining in this study. Study design: Fourteen female Wistar Albino rats of 12 weeks were randomly divided into two groups. Abdomen midline incision was conducted under general anesthesia. Group 1(G1) (n = 7): Group in which only the abdomen was opened and closed, Group 2(G2) (n = 7): Group that underwent right total salpingectomy. After 1 month, abdomens of all rats were opened. Ovaries were macroscopically evaluated. Right ovarian tissue was quickly removed, fixed in 10% formaldehyde, and paraffin blocks were prepared.' The existence of fibrosis was identified with the usage of light microscope. Follicles were microscopically classified and counted. The prevalence of cytoplasmic immune staining and TUNEL staining was scored semi-quantitatively. Statistical analysis: : SPSS 17.0 software was used for the statistical analysis of data. First, Kruskal-Wallis variance analysis was conducted, and then Mann-Whitney U test was utilized for inter-group dual comparisons for parameters found as p < 0.05. Results: While the number of CL was found out dramatically high, secondary follicle count was found out to be significantly low in G2. Also in G2, although the number of atretic follicle and fibrosis were found out significantly increased, and the score of the angiogenesis was found to be significantly decreased in CL When compared PCNA immunoreactivity in granulosa cells with the control group, there was a significant decrease in G2. When compared the malondialdehyde (MDA) immunoreactivity with G1 a significant increase was established in G2. Apoptosis score of ovarian follicles in granulosa cells was significantly higher in G2. Conclusions: In this experimental study, the decrease in the ovarian reserve and PCNA staning of granulosa cells, an increase in apoptosis, fibrosis and the number of atretic follicles in unilateral total salpingectomy operation were analyzed in rats. We found out significantly higher MDA staining rates in G2 in comparison to in G1. According to the study, the unilateral total salpingectomy procedure can damage to the same side ovarian tissue by means of the ischemia and reperfusion injuiy at the ovarian tissue. (C) 2015 Elsevier Ireland Ltd. All rights reserved.
Keywords: Salpingectomy; Ovarian reserve; PCNA; Apoptosis; Malondialdehyde